Should Developers Build Convertible Parking Structures? Or Are They Just a Public Sector Investment?. Issue 1 (1st January 2020) - Simons, Robert A.
Abstract: Developers of urban parking decks—either stand-alone or ancillary to other uses like office, retail or housing—will soon face a decision brought on by the advent of driverless vehicles (DV): maximize short term cash flow and risk that these structures' useful life will be cut short, or build sustainably and make them convertible to other land uses, thus extending useful life. Sustainable investment often involves higher up-front costs to preserve building life and therefore residual value in the long run. It may also require higher maintenance costs and lower cash flows to achieve the same goals. Thus any sustainable benefits from building reuse are essentially eliminated in present value terms, potentially leading to wasteful investment. With driverless cars and decreased parking demand as a frame of reference, this paper uses financial simulation modeling to look at the issue in the context of sustainable parking garages, and explores ways to predict the who, when, and where of upcoming investment parking structure decisions. Alternative paradigms for decision making (mini-max as opposed to purely profit maximization) are also explored. We find that under likely future market conditions for parking, developers will be hard pressed to make their required investment returns on new parking structures for holding periods of longer than 10 years on convertible structures, likely leaving the field to the public sector.